Correction: Dye colour switching by hydride-terminated silicon particles and its application as an oxygen indicator. Issue 20 (6th May 2016) - Ye, Miaomiao; Qian, Chenxi; Sun, Wei; He, Le; Jia, Jia; Dong, Yuchan; Zhou, Wenjie
Abstract : Correction for 'Dye colour switching by hydride-terminated silicon particles and its application as an oxygen indicator' by Miaomiao Ye et al., J. Mater. Chem. C, 2016, DOI: ; Web:10.1039/c6tc00749j .